Surface uplift and convective rainfall along the southern Central Andes (Angastaco Basin, NW Argentina) - Pingel, Heiko (2016)
Stable-isotopic and sedimentary records from the orogenic Puna Plateau of NW Argentina and adjacent intermontane basins to the east furnish a unique late Cenozoic record of range uplift and ensuing paleoenvironmental change in the south-central Andes. Today, focused precipitation in this region occurs along the eastern, windward flanks of the Eastern Cordillera and Sierras Pampeanas ranges, while the orogen interior constitutes high-elevation regions with increasingly arid conditions in a westward direction. As in many mountain belts, such hydrologic and topographic gradients are commonly mirrored by a systematic relationship between the oxygen and hydrogen stable isotope ratios of meteoric water and elevation. The glass fraction of isotopically datable volcanic ash intercalated in sedimentary sequences constitutes an environmental proxy that retains a signal of the hydrogen-isotopic composition of ancient precipitation. This isotopic composition thus helps to elucidate the combined climatic and tectonic processes associated with topographic growth, which ultimately controls the spatial patterns of precipitation in mountain belts. However, between 25.5 and 27°S present-day river-based hydrogen-isotope lapse rates are very low, possibly due to deep-convective seasonal storms that dominate runoff. If not accounted for, the effects of such conditions on moisture availability in the past may lead to misinterpretations of proxy-records of rainfall. Here, we present hydrogen-isotope data of volcanic glass (δDg), extracted from 34 volcanic ash layers in different sedimentary basins of the Eastern Cordillera and the Sierras Pampeanas. Combined with previously published δDg records and our refined U-Pb and (U-Th)/He zircon geochronology on 17 tuff samples, we demonstrate hydrogen-isotope variations associated with paleoenvironmental change in the Angastaco Basin, which evolved from a contiguous foreland to a fault-bounded intermontane basin during the late Mio-Pliocene. We unravel the environmental impact of Mio-Pliocene topographic growth and associated orographic effects on long-term hydrogen-isotope records of rainfall in the south-central Andes, and potentially identify temporal variations in regional isotopic lapse rates that may also apply to other regions with similar topographic boundary conditions.